Brenda Palms Barber : helping to build a future - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2023)
North Lawndale is a neighborhood of Chicago that is one of the most impoverished areas of the region, with higher than average crime and lower than average job opportunities. Brenda Palms Barber grew up in Portland, Oregon. When her grandparents moved there from Texas, they were one of the 10 black families in the community at the time. Brenda's parents were divorced when Brenda was very young, leaving her mom, now a single parent, to raise four girls while working full time. Brenda vowed to be a helper to her mother. This is the story of Brenda Palms Barber, from being a helper to her mom to becoming one of Chicago's most notable leaders and executives. Brenda's work in the creation and development of the North Lawndale Employment Network and Sweet Beginnings has provided behavior training and jobs for a large number of formerly incarcerated men and women in the Lawndale area. This case reviews her life and creative approach to finding employment and hope for those others would not hire.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Barber, Brenda Palms; Employment agencies -- Social aspects -- Illinois -- Chicago -- Case studies; Poor -- Employment -- Illinois -- Chicago -- Case studies; Ex-convicts -- Employment -- Chicago -- Case studies; North Lawndale (Chicago, Ill.) -- Social conditions -- Case studies